EVALUATION OF USE DIFFERENT DESIGNS TROLLEY AT AN INCREASED VELOCITY OF THE ELECTRICAL TRACTION ROLLING STOCK - , А. В. (Municipal economy of cities. Series: «Economy science», 2013)
Actuality of conducting of dynamic researches is grounded on determination of high speeds of motion of elektrotyagovogo rolling stock on the terms of providing of high-quality current collection. The results of mathematical design of dynamic  co-operation of currentremoval device of the known constructions are represented with a contact wire at the different rates of movement of elektrotyagovogo rolling stock. Results which confirmed to expedience the uses of new construction of currentremoval device for mobile composition of new generation are shown.